Pharmacological characterization of the sodium-glicose co-transporter 2 inhibitors, gliflozins in isolated platelets from healthy volunteers - Torres, Pedro Henrique Portugal; Iglesias, Fabiola Taufic Monica; Lescano, Caroline Honaiser (Revista dos Trabalhos de Iniciação Científica da UNICAMP, 2019)
Gliflozins are a new pharmacological class of drug approved to treating patients with type 2 diabetes and act by inhibiting the sodium-glucose co-transporter 2 (SGLT2) on the epithelial cells of the proximal convoluted tubule of the kidneys. Cardiovascular diseases (CVDs) are a major challenge in the management of type 2 diabetes mellitus, and Gliflozins have shown to improve cardiovascular and renal outcomes in subjects with type 2 diabetes presenting cardiovascular diseases. The mechanism by which cardiovascular protection is attributed to gliflozins remains unknown, although there is some research about a hypothetical effect in the myocardial cells. Although platelets are essential for human homeostasis the cells fragments are involved in the pathophysiology of cardiovascular-related diseases. Therefore, the aim of this study is to carry out a pharmacological characterization of the gliflozins (empagliflozin, canagliflozin and dapagliflozin) available on the market in isolated platelets from helathy volunteers. All the experimental protocols were approved by the Ethic Committee from UNICAMP (Number 2.412.312). Our preliminary results showed that markedly inhibited platelet aggregation-challenged by collagen and ADP, although to a lesser extent, also reduced platelet aggregation challenged by U-46619 and thrombin. Moreover, the addition of low concentrations of endothelial mediators potentiated the effects of gliflozins on platelet inhibition.